2020
DOI: 10.3390/ijms21134788
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP1 Inflammasome in Human Skin and Beyond

Abstract: Inflammasomes represent a group of protein complexes that contribute to host defense against pathogens and repair processes upon the induction of inflammation. However, aberrant and chronic inflammasome activation underlies the pathology of numerous common inflammatory diseases. Inflammasome assembly causes activation of the protease caspase-1 which in turn activates proinflammatory cytokines and induces a lytic type of cell death termed pyroptosis. Although NLRP1 (NACHT, leucine-rich repeat and pyrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 129 publications
(217 reference statements)
1
69
0
Order By: Relevance
“… 162 , 416 418 Surprisingly, talabostat induces CARD8-mediated pyroptosis in THP-1 and other AML cells, which is independent of NLRP1, indicating that CARD8 can also form inflammasome. 413 , 419 , 420 It has been found that DPP8/9 inhibitors induce pyroptosis in the vast majority of human acute myeloid leukemia (AML) cell lines, and these inhibitors suppress the progression of human AML in mouse models. 162 , 413 What’s more, CARD8 was involved in the pyroptosis of human myeloid cells induced by DPP8/9 inhibitors, which provided a new potential strategy for the treatment of AML.…”
Section: Role Of Pyroptosis In Tumorsmentioning
confidence: 99%
“… 162 , 416 418 Surprisingly, talabostat induces CARD8-mediated pyroptosis in THP-1 and other AML cells, which is independent of NLRP1, indicating that CARD8 can also form inflammasome. 413 , 419 , 420 It has been found that DPP8/9 inhibitors induce pyroptosis in the vast majority of human acute myeloid leukemia (AML) cell lines, and these inhibitors suppress the progression of human AML in mouse models. 162 , 413 What’s more, CARD8 was involved in the pyroptosis of human myeloid cells induced by DPP8/9 inhibitors, which provided a new potential strategy for the treatment of AML.…”
Section: Role Of Pyroptosis In Tumorsmentioning
confidence: 99%
“…However, UVB irradiation does induce IL-1β release in murine skin, which is mediated by infiltrating professional immune cells (mainly dendritic cells) and not keratinocytes [ 87 ]. These result show the poor conservation of the NLRP1 pathway between human and mouse skin [ 108 ]. Interestingly, 3C proteases and dsRNA only activate human NLRP1, whereas Anthrax Lethal Factor metalloprotease induces cleavage of murine Nlrp1b but not the human form [ 109 ].…”
Section: The Nlrp Subfamilymentioning
confidence: 99%
“…T. gondii infection and Dpp8/9 inhibition with Talabostat (Val-boroPro) commonly activated both murine and human isoforms. Interestingly, Talabostat activates CARD8 in THP-1 cell-lines but triggers NLRP1 activation in keratinocytes, despite both cell types expressing both sensors [ 108 ].…”
Section: The Nlrp Subfamilymentioning
confidence: 99%
See 1 more Smart Citation
“…In HPKCs, it has been demonstrated previously that NLRP1 can function as principal inflammasome sensor (31). UVB radiation induces its activation in keratinocytes, which is a key element of the skin's photodermatitis/sunburn response (31,37,38). However other studies have also implicated the NLRP3 inflammasome (29,39).…”
Section: E H) Of Note Il-1ßmentioning
confidence: 99%